Qualitative Detection Toward Military and Improvised Explosive Vapors by a Facile TiO2 Nanosheet-Based Chemiresistive Sensor Array - Li, Yushu; Zhou, Wenyi; Zu, Baiyi; Dou, Xincun (Frontiers in Chemistry, 2020)
A facile TiO2 nanosheets-based chemiresistive gas sensor array was prepared to identify 11 kinds of military and improvised explosive vapors at room temperature. The morphology of TiO2 nanosheets was well controlled by adjusting the concentration of HF applied during the preparation. Owing to the morphology difference, the TiO2 nanosheet-based sensors show different response values towards 11 kinds of explosives, which is the basis of the successful discriminative identification. This method owes lots of advantages over other detection techniques, such as the facile preparation procedure, high response value (115.6% for TNT and 830% for PNT) at room temperature, rapid identifying properties (within 30 s for 9 explosives), simple operation, high anti-interference property and low probability of misinforming, and consequently has a huge potential application in the qualitative detection of explosives.